Bilingualism: Choices to be Made - Mažuolienė, Zita; Jankūnienė, Ana (Verbum, 2013)
The present research focuses on parents’ decision to raise children with more than one language. Bilingualism in this article is considered to be not a result of environmental pressure or linguistic situation but the conscious choice made by the child’s parents. The article concentrates on three main steps in planning the child’s linguistic development: the choice of the language of pre-school (kindergarten) institution, the choice of the language of schooling, and parents’ choice to include non-formal language learning activities into the child’s daily routine. The research states that parents’ attitude towards teaching their children a non-native language depends on the linguistic group they belong to and their educational background. The results of the research confirm that lack of methodological knowledge prevents parents from or limits their ability to teach the child. The survey also proves that children whose parents do teach them non-native languages are more motivated and more successful at school than their peers. Therefore, careful planning of the child’s linguistic development is of primary importance and needs professional support from educational institutions.